Find ways for rule of law : India's ex-chief justice Altamas Kabir tells discussion in Dhaka - The Daily Star (The Daily Star, 2014)
The Talk on Access to Justice For All by Honorable Justice Altamas Kabir, former Chief Justice of India, organised by BRAC Institute of Governance and Development on 24th April 2014 at the Daily Star Centre.